The role of movability on campus outdoor furniture - Pezeshkpoor, Zhila (Kansas State University, 2020)
Public spaces are platforms where people can be a part of the public realm. One of the most important aspects of public spaces is creating essential opportunities for social interactions. This functional feature of public space is identified as “sociability.” University campuses are among the popular public spaces in many cities, where students, faculty, staff, and many other residents spend time in order to get to their offices, attend a meeting, or even eat a meal. In small college towns, campuses are the center of social interactions. Along with its educational function, one purpose of a successful campus is to bring people together in an environment that creates the potential for intellectual and social exchange. While the physical character and quality of campus are defined by both its buildings and open spaces, it is the open space that has the greatest potential for unifying and equalizing the shared space of the campus. Comprised of streets, walkways, greens, courtyards, plazas, and gardens, open space has the potential to knit together the diverse elements of the campus in a coherent way. Campus planning is more important than the past because the evolution of campuses is now contributing to identifying and reinforcing an institution’s brand. In response to the growing need for student life and involvement, university and college leaderships are competing against one another to develop their campuses and better suit what their students want. This research focuses on campus furniture which serves as an influential campus element. Public furniture is a rarely observed topic in the planning literature. The term furniture is usually associated with the private sphere, while the campus is a public space. Furniture on campus provides students with comfort, information, seating, light, and protection. It ensures a place is live, accessible and enriching for its community. The campus furniture creates a deeper bond between the university and the surrounding. Therefore, campus furniture, with emphasis on movable chairs and furniture, is the central topic of inquiry in this research. This study aims at investigating various criteria and elements that direct the process of decision making in campus planning in selected case studies to better understand why some campuses use specific type(s) of furniture and some do not. The main research question of this study is: What are the most important elements that campus planners consider in (not) choosing movable campus furniture? Using a qualitative research approach, this research aims at finding an answer to this question. While the principal methodological framework in this research is the case study, semi-structured interviews and document analysis are primary data collection methods. Along with the interview, indeed, document analysis is a complementary method implemented to gain background information about campuses, their planning goals, strategies, and design policies and plans. Significant documents that are used in this research are campus master plans, campuses websites, and campus maps. Four university campuses are reviewed and analyzed in this research: Kansas State University (KSU) in Manhattan, Kansas; the University of Kansas (KU) in Lawrence, Kansas; the University of Nebraska (UNL) at Lincoln, Nebraska; and the University of Missouri at Kansas City (UMKC).
Keywords: Campus planning; Movable street furniture